2018
DOI: 10.1093/jme/tjx258
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Geographic Distribution of Borrelia miyamotoi in Host-Seeking Ixodes pacificus (Acari: Ixodidae) Nymphs in Mendocino County, California

Abstract: Borrelia miyamotoi is an increasingly recognized human pathogen transmitted by Ixodes ticks in the Northern Hemisphere. In North America, infection prevalences of B. miyamotoi are characteristically low (<10%) in Ixodes scapularis (Say; Acari: Ixodidae) and Ixodes pacificus (Cooley & Kohls; Acari: Ixodidae), both of which readily bite humans. We tested 3,255 host-seeking I. pacificus nymphs collected in 2004 from 79 sites throughout Mendocino County in north-coastal California for presence of B. miyamotoi. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 56 publications
1
14
0
1
Order By: Relevance
“…miyamotoi is found in approximately 1% of I . pacificus nymphs and adults in California [12, 54]. While there is evidence of B .…”
Section: Discussionmentioning
confidence: 99%
“…miyamotoi is found in approximately 1% of I . pacificus nymphs and adults in California [12, 54]. While there is evidence of B .…”
Section: Discussionmentioning
confidence: 99%
“…Among 20 studies found in this review, from countries reporting clinical cases and B. miyamotoi prevalence in ticks, infectionrates in ticks ranged from 0.02 to 6.4%, although most studies reported a range between 1 and 2% (Table 1) [3,5,15,18,19]. Nevertheless, pockets of higher infection rates have been described.…”
Section: Resultsmentioning
confidence: 95%
“…Nevertheless, pockets of higher infection rates have been described. In Napa County, California, US, for example, 15.4% of adult ticks (10/65 I. pacificus ) studied were infected with B. miyamotoi [3] compared with a background infection level of 1.4% (44/3,255) of nymphs of this same species [19]. Moreover, in a study in Kurgan, Russia, 16% of ticks (26/162 I. persulcatus ) were found infected [2].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations